Formative research strengthening in higher education institutions of Risaralda (2022)
Formative research plays a pivotal role in the development and progress of higher education institutions, empowering students to enhance their academic skills, improve methodologies, and foster an environment of innovation and excellence. In the context of Risaralda, a region renowned for its commitment to education, the significance of formative research cannot be overstated. This book, “Formative Research Strengthening in Higher Education Institutions of Risaralda,” serves as a comprehensive exploration of the various dimensions and applications of formative research within the educational landscape. It also places the protagonist of formative research in the foreground of the scene, the students. They are the authors of the chapters that created this book. Edgar Allan Poe once write that “the principal source of error in all human investigations lay in the liability of the understanding to under-rate or to over-value the importance of an object, through mere mis-admeasurement of its propinquity.” (The Sphinx, 1850) This quote emphasizes the crucial role that research plays in overcoming these inherent human biases and misconceptions. Research provides a systematic and disciplined approach to investigating and understanding the world around us. It enables us to bridge the gap between our initial perceptions and the actual importance of an object, idea, or phenomenon. By delving into the depths of knowledge and exploring various perspectives, research allows us to gain a more accurate and comprehensive understanding of the subjects under investigation. Teaching research is one of the most significant and challenged subjects that a professor had, because is very difficult to teach something that need to be taught with experience. But this book completes the challenge and show that research can be taught in these educational institutions. One of the examples are the chapters that were written by students in this book, that shows the level of learning that they have. The England Sociologist Anthony Giddens explains the important of methodology in the research path and said that “The difference is similar to that which exists between the recipes in a cookbook and the actual process of preparing a dish. Experienced chefs often cook without relying entirely on the recipe, but their results can be better than those who follow the instructions”. That’s why research is a process where students develop their own identity in the academic ecosystem.